2016
DOI: 10.1371/journal.pone.0164951
|View full text |Cite
|
Sign up to set email alerts
|

Time-Course of Muscle Mass Loss, Damage, and Proteolysis in Gastrocnemius following Unloading and Reloading: Implications in Chronic Diseases

Abstract: BackgroundDisuse muscle atrophy is a major comorbidity in patients with chronic diseases including cancer. We sought to explore the kinetics of molecular mechanisms shown to be involved in muscle mass loss throughout time in a mouse model of disuse muscle atrophy and recovery following immobilization.MethodsBody and muscle weights, grip strength, muscle phenotype (fiber type composition and morphometry and muscle structural alterations), proteolysis, contractile proteins, systemic troponin I, and mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
105
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(118 citation statements)
references
References 54 publications
12
105
0
Order By: Relevance
“…Regarding the mechanism underlying the loss of specific force, it is shown that the reduction in myosin protein content accompanies the loss of specific force during muscle unloading (Figure ) . It is consistent with the finding that the extent of atrophy directly corelated with myosin concentration and reduction in specific force .…”
Section: Methodssupporting
confidence: 85%
“…Regarding the mechanism underlying the loss of specific force, it is shown that the reduction in myosin protein content accompanies the loss of specific force during muscle unloading (Figure ) . It is consistent with the finding that the extent of atrophy directly corelated with myosin concentration and reduction in specific force .…”
Section: Methodssupporting
confidence: 85%
“…The rationale to use such methodologies was to identify a pure population of muscle progenitors as demonstrated in previous studies (Yin, Rice, & Rudnicki, ). In fact, one of the main goals in the study was to characterize the gene expression profile of the isolated progenitor cells during recovery following a period of hindlimb muscle disuse for 7 days, which was defined as a key time‐point to analyze early and late events as previously shown in this experimental model (Chacon‐Cabrera et al, ; Chacon‐Cabrera, Gea, et al, ). Furthermore, the use of methodologies such as histological procedures enabled us to define the localization and numbers of active and proliferating satellite cells in the study muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were exposed to unilateral hindlimb immobilization as previously described to reproduce a model of disuse muscle atrophy (Chacon‐Cabrera et al, ; Chacon‐Cabrera, Gea, et al, ). Briefly, the left hindlimb was shaved with clippers and was enveloped using surgical tape.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations